Exploring the talent mobility issue: Towards an intelligent system - Ismail, N.N.B. (Institute of Electrical and Electronics Engineers Inc., 2016)
High attrition rate might cause harm to an organization. The attrition rate can be reduced by implementing retention exercises. However in order to implement the retention exercises, an in-depth understanding about the issue is vital. This is due to the fact that there are many factors that contribute to the attrition and retention. It is important to ensure that the retention exercises must be tally with the reason of attrition so that the problem could be solved. Therefore, in this paper, a survey was conducted to find the main issues of attrition in a selected institution. From the findings it shows that talent mobility or career movement is one of the main issues that lead to attrition issue in the institution. Face to face interviews were then conducted with selected technical and non-executives employees of the institution to get a clearer idea of the mobility issue. From the interview, we manage to gather some data that gave insights to how an intelligent system could be designed. It is hoped that the results of this study will allow future research into how retention could be reduced with the assistance of intelligent agents. Â© 2016 IEEE.